Музей-заповедник "Лудорвай" - Тарануха Галина Владимировна (Удмуртия, 2018)
Экземпляры: (20200917) / Инвентарный номер: 2274 / Цена: / Сис.шифр: 26.89(2Рос.Удм) / Авт.знак: М 90 / ГРНТИ: 39.19 / ББК: 26.89(2Рос.Удм)